El coaching como modelo de gestión en Talento Humano (2017)
In the present work a conceptual theoretical framework on coaching will be made as a management model for the growth, development and training of human talent in organizations, because in the business environment, better skills of development, leadership, responsibility, commitment, strategy, initiative and proactivity. In order to do this, we will take into account information that allows us to publicize the importance of coaching on a personal and business level; as a fundamental basis of management models because they allow a guide and an accompaniment to reach the goals and objectives proposed by an organization.